An update on the best approaches to prevent complications in penile prosthesis recipients. (January 2019) - Krzastek, Sarah C.; Smith, Ryan
Placement of inflatable penile prosthesis is a procedure frequently performed for medication-refractory erectile dysfunction. Device implantation is not without risks, and as the frequency of device implantation increases, so do associated complications. The aim of this work is to review the most frequent operative complications associated with implantation of inflatable penile prostheses, and to review the best approaches to prevent these most common complications. Complications can broadly be categorized as infectious, noninfectious tissue-related, device-related, or related to patient and partner satisfaction. With understanding of these complications and ways to avoid them, as well as with appropriate patient selection and counseling, the inflatable penile prosthesis is an excellent option for the treatment of erectile dysfunction.